Relative efficacy of spironolactone, eplerenone, and cAnRenone in patients with chronic heart failure (RESEARCH): a systematic review and network meta-analysis of randomized controlled trials - Frankenstein, Lutz; Seide, Svenja; Täger, Tobias; Jensen, Katrin; Fröhlich, Hanna; Clark, Andrew L.; Seiz, Mirjam; Katus, Hugo; Nee, Paul; Uhlmann, Lorenz; Naci, Huseyin; Atar, Dan (Heart failure reviews, 2020)
This study aims to assess the comparative benefit and risk profile of treatment with mineralocorticoid receptor antagonists (MRAs) with regard to all-cause mortality (primary endpoint), cardiovascular mortality, or heart failure (HF)-related hospitalization (secondary endpoints) and the safety endpoints hyperkalemia, acute renal failure, and gynecomastia in patients with chronic HF. We conducted a systematic review and network meta-analysis following PRISMA-P and PRISMA-NMA guidelines. From 16 different sources, 14 randomized controlled trials totaling 12,213 patients testing an active treatment of either spironolactone, eplerenone, or canrenone/potassium-canreonate in adults with symptomatic HF due to systolic dysfunction reporting any of the above endpoints were retained. Efficacy in comparison to placebo/standard medical care with respect to all-cause mortality was confirmed for spironolactone and eplerenone while no conclusion could be drawn for canrenone (HR 0.69 (0.62; 0.77), 0.82 (0.75; 0.91), and 0.50 (0.17; 1.45), respectively). Indirect comparisons hint a potential (non-significant) preference of spironolactone over eplerenone (HR 0.84 (0.68; 1.03)). The overall risk of bias was low to intermediate. Results for secondary endpoints as well as sensitivity analyses essentially mirrored these findings. The beta-blocker adjusted meta-analysis for the primary endpoint showed the same tendency as the unadjusted one (HR 0.39 (0.07; 2.03)). Results need to be interpreted with caution, though, as the resultant mix of patient- and study-level covariates produced unstable statistical modeling. We found no significant and systematic superiority of either MRA regarding efficacy toward all endpoints considered in both direct and indirect comparisons.
Published online: 30 July 2019
Gesehen am 14.04.2020